STRATEGI MANAJEMEN PEMASARAN UNTUK MENINGKATKAN PENJUALAN PRODUK USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI LEMBAGA PEMASYARAKATAN - Indra Biantong; Graciella Devi Maharani (JUSTITIA : Jurnal Ilmu Hukum dan Humaniora, 2020)
Indonesia is known as a nation that is abundant in natural and human resources. This abundant resource has become a great opportunity for improving the economy of the Indonesian people with Micro, Small and Medium Enterprises (MSMEs). MSME is an important effort in the national. At this time, MSMEs are intensively run in various regions in Indonesia including in the Penitentary. Since 2005, the level of sales of MSME products has increased. Thus, to penetrate and maintain MSMEs a marketing strategy is needed. Marketing strategy is the main thing in the business process, the following are important things that can improve and be able to improve MSME products, among others: strategy in making new changes that are made according to the needs and demands of consumers, supply strategies market needs with market expectations that will seek the opposite product, a strategy related to prices in accordance with market needs, the ability to adjust to economic and social problems of consumers, which also facilitates the ability of a product to provide value assessments to consumers, and SWOT analysis. With these strategies, it is expected that the prison entrepreneurship products produced by MSMEs will be able to improve their products in the local market. In this study using descriptive qualitative research and literature study data collection techniques. The research objective is to study how marketing management strategies to increase product sales of Micro and Small and Medium Enterprises in Penitentiary. It is hoped that this research has toeritis and practical benefits that will help in implementing marketing strategies in developing MSMEs in Lembaga Pemasyarakatan.